Theologie, Philosophie und Mystik im zwölferschiitischen Islam des 9./15. Jahrhunderts : Die Gedankenwelten des Ibn Abī Ǧumhūr al-Aḥsā'ī (um 838/1434/35 - nach 906/1501) - Schmidtke, Sabine (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
This volume focuses on the theological views of the Imāmī Shī'ite theologian Muḥammad b. 'Alī b. Ibrāhīm b. Abī Jumhūr al-Aḥsā'ī (d. after 906/1501), who combined traditional thought of the Mu'tazilites with the philosophical tradition of Ibn Sīnā (d. 428/1037), with the Illuminationist ( Ishrāqī ) tradition of Shihāb al-Dīn al-Suhrawardī (executed in 587/1191 and his followers, and with the speculative mysticism of Ibn al-'Arabī (d. 638/1204). Ibn Abī Jumhūr moreover attempted to harmonize traditional Shī'ite views which were deeply influenced by the Mu'tazilite traditional with typical Ash'arite notions. The book sets out to investigate thoroughly the impact of the various traditions on the theological views of Ibn Abī Jumhūr. It further investigates the place of this theologian within the development of Shī'ite theological thought. The volume also includes a comprehensive study of Ibn Abī Jumhūr as well as a detailed bibliographical examination of his writings.